Contributions of bibliometrics to the study of interdiscipline. A methodology for the analysis of the intersection between the fields of neurosciences and computational sciences - Méndez Isla, Malena; Mauro, Agustin; Kozlowski, Diego (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Despite the growing importance of interdisciplinary studies for the development of science, quantitative works on the subject are not abundant. Bibliometrics offers tools to analyze interdisciplinarity through a complementary approach to qualitative work. While there is a body of precedents in bibliometrics (1,2,3,4,5,6), methodological proposals for the construction of databases of the intersection of two disciplines are scarce.(7) Thus, a proposal is made to identify an interdisciplinary field with a set of scholarly articles. The objective of this work is to develop a methodology for defining the intersection between the fields of neuroscience and computational science. This area of study is not directly traceable from categorizations in databases. For this reason, three strategies are built to delimit an interdisciplinary corpus and compare the potential and limitations of each of them. The three strategies are focused, on the one hand, on keywords and, on the other hand, on citation and reference patterns using the Web Of Science database. It is found that it is possible to operationalize the interdiscipline with two types of approaches: 1. A semantic approach based on the use of keywords. A relational approach focusing on cross-references and citations between articles from the two disciplines. As a result, a basis for the study of the intersection between the fields of neurosciences and computational sciences from a bibliometric perspective is obtained, and a methodological proposal for the quantitative study of interdiscipline in other areas of knowledge is mad